Characterization and FEA evaluation of a ZrB2–SiC ceramic containing TaC for beam–column joint application. Issue 8 (15th April 2021) - Mohammadzadeh, Behzad; Jung, Sunghoon; Lee, Tae Hyung; Cha, Joo Hwan; Park, Jongseong; Asl, Mehdi Shahedi; Jang, Ho Won; Lee, Sea-Hoon; Shokouhimehr, Mohammadreza; Kang, Junsuk
Abstract: An ultra-high temperature composite with superior mechanical characteristics was developed using zirconium diboride (ZrB2, 60% by volume), silicon carbide (SiC, 30% by volume), and tantalum carbide (TaC, 10% by volume), and its microstructure characteristics and mechanical properties were obtained experimentally by nanoindentation testing, X-ray diffraction, field emission scanning electron microscopy, X-ray fluorescence analysis, and X-ray photoelectron spectroscopy. Oxide contamination was eliminated, and the ceramic was densified to achieve a fully-dense ternary compound. To assess its performance in a typical real-world application, a finite element analysis was performed using the commercially available ABAQUS package for a one-bay one-story steel frame in which the prepared ceramic was used for the beam–column joint reinforcement end-plates; a good agreement was found with the results reported in the literature for comparable structures. The performance of a steel frame with a plate prepared from functionally graded materials located at the beam–column joint was then modeled in ABAQUS and subjected to the conditions recorded during a 1940 earthquake with a magnitude of 7.7. The results show that the utilized ceramic significantly enhanced the structural behavior of the reinforced concrete frame, confirming its potential utility in a wide range of industrial, structural, and medical applications.